2022
DOI: 10.3389/fphar.2022.887402
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Lymphatics for Nanoparticle Drug Delivery

Abstract: The lymphatics transport material from peripheral tissues to lymph nodes, where immune responses are formed, before being transported into systemic circulation. With key roles in transport and fluid homeostasis, lymphatic dysregulation is linked to diseases, including lymphedema. Fluid within the interstitium passes into initial lymphatic vessels where a valve system prevents fluid backflow. Additionally, lymphatic endothelial cells produce key chemokines, such as CCL21, that direct the migration of dendritic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…We formulated 40–150 nm PEGylated nanoparticles , from unmodified 103 ± 5 and 40 ± 2 nm. 100 and 40 nm nanoparticles were selected for this study as they lie within the 10–250 nm size range reported to enter lymphatic vessels and transport to lymph nodes. , Addition of PEG increased nanoparticle hydrodynamic diameter to 122 ± 6 nm (partial PEG) and 142 ± 3 nm (dense PEG) and 43 ± 2 nm (partial PEG) and 49 ± 3 nm (dense PEG) (Figure S1A). PEGylated nanoparticles also displayed a near-neutral ζ – potential (Figure S1B).…”
Section: Resultsmentioning
confidence: 99%
“…We formulated 40–150 nm PEGylated nanoparticles , from unmodified 103 ± 5 and 40 ± 2 nm. 100 and 40 nm nanoparticles were selected for this study as they lie within the 10–250 nm size range reported to enter lymphatic vessels and transport to lymph nodes. , Addition of PEG increased nanoparticle hydrodynamic diameter to 122 ± 6 nm (partial PEG) and 142 ± 3 nm (dense PEG) and 43 ± 2 nm (partial PEG) and 49 ± 3 nm (dense PEG) (Figure S1A). PEGylated nanoparticles also displayed a near-neutral ζ – potential (Figure S1B).…”
Section: Resultsmentioning
confidence: 99%
“…Particle size plays a pivotal role in optimizing lymphatic drug delivery [ 18 ]. Larger nanoparticles (>100 nm in diameter) and microparticles tend to be trapped in the interstitial matrix at the injection site or require phagocytosis by tissue dendritic cells or Langerhans cells for cell-mediated delivery to the lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our work demonstrated that PEG density is an important consideration that modulates nanoparticle transport into lymphatic vessels. For further considerations in design criteria for lymphatic drug delivery, we point the readers to a recent review ( 77 ).…”
Section: Nanotechnology-enabled Lymphatic Vessel Targetingmentioning
confidence: 99%